Morphological change of coiled bacterium Spirosoma linguale with acquisition of β-lactam resistance - Tomoya Maeda (Nature Portfolio, 2021)
Abstract Spirosoma linguale is a gram-negative, coiled bacterium belonging to the family Cytophagaceae. Its coiled morphology is unique in contrast to closely related bacteria belonging to the genus Spirosoma, which have a short, rod-shaped morphology. The mechanisms that generate unique cell morphology are still enigmatic. In this study, using the Spirosoma linguale ATCC33905 strain, we isolated β-lactam (cefoperazone and amoxicillin)-resistant clones. These clones showed two different cell morphological changes: relatively loosely curved cells or small, horseshoe-shaped cells. Whole-genome resequencing analysis revealed the genetic determinants of β-lactam resistance and changes in cell morphology. The loose-curved clones commonly had mutations in Slin_5958 genes encoding glutamyl-tRNA amidotransferase B subunit, whereas the small, horseshoe-shaped clones commonly had mutations in either Slin_5165 or Slin_5509 encoding pyruvate dehydrogenase (PDH) components. Two clones, CFP1ESL11 and CFL5ESL4, which carried only one mutation in Slin_5958, showed almost perfectly straight, rod-shaped cells in the presence of amoxicillin. This result suggests that penicillin-binding proteins targeted by amoxicillin play an important role in the formation of a coiled morphology in this bacterium. In contrast, supplementation with acetate did not rescue the growth defect and abnormal cell size of the CFP5ESL9 strain, which carried only one mutation in Slin_5509. These results suggest that PDH is involved in cell-size maintenance in this bacterium.